2021
DOI: 10.1080/07853890.2021.1875498
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ilio-psoas haematomas (IPHs): a warning for COVID-19 inpatients

Abstract: Introduction Critically ill patients with COVID-19 are at increased risk of developing a hypercoagulable state due to haemostatic changes directly related to the SARS-CoV-2 infection or to the consequence of the cytokine storm. Anticoagulation is now recommended to reduce the thrombotic risk. Ilio-psoas haematoma (IPH) is a potentially lethal condition that can arise during the hospitalization, especially in intensive care units (ICUs) and frequently reported as a complication of anticoagulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 18 publications
0
43
0
3
Order By: Relevance
“…4,5 Some cases of spontaneous hematomas involving the iliopsoas muscle, neck, abdominal wall, and chest wall have also been reported. [13][14][15] The risk of bleeding is relatively high in COVID-19 patients, especially in those who have received therapeutic anticoagulation treatment, and this condition is usually associated with an increased risk of mortality. 16 However, Mattioli et al 4 reported a case of neck and upper chest spontaneous hematoma in an 84-year-old patient who was receiving prophylactic doses of LMWH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Some cases of spontaneous hematomas involving the iliopsoas muscle, neck, abdominal wall, and chest wall have also been reported. [13][14][15] The risk of bleeding is relatively high in COVID-19 patients, especially in those who have received therapeutic anticoagulation treatment, and this condition is usually associated with an increased risk of mortality. 16 However, Mattioli et al 4 reported a case of neck and upper chest spontaneous hematoma in an 84-year-old patient who was receiving prophylactic doses of LMWH.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Some cases of spontaneous hematomas involving the iliopsoas muscle, neck, abdominal wall, and chest wall have also been reported. 13 15 …”
Section: Discussionmentioning
confidence: 99%
“…5, performed according to PRISMA criteria, 21 17 studies were included in qualitative and quantitative syntheses. 16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The systematic review identified 40 patients with COVID-19 complicated by muscular hematomas.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The bleeding risk of each individual patient needs to be considered prior and during the implementation of any of these strategies given that anticoagulation, especially when systemic, may increase the propensity for bleeding. A case series from Italy, for example, described the case of seven patients admitted to the hospital with COVID-19 who presented spontaneous ilio-psoas hematoma as a consequence of either prophylactic or therapeutic anticoagulation with LMWH [109]. None of these patients were receiving KRT.…”
Section: Anticoagulationmentioning
confidence: 99%